Macroeconomic adjustment : policy instruments and issues - Davis, Jeffrey M.; IMF Institute (Washington, D.C. : IMF Institute, International Monetary Fund, 1992)
This IMF publication provides an introductory review of some of the policy issues, relating to monetary, fiscal, exchange rate, trade, external debt and supply-oriented policies.
"August 1992."
Includes bibliographical references.
gp. 23/01/2019
Loan
Keywords: Economic stabilization; Economic development; Economic policy